University students’ perception towards online learning in biology - N. Nurdiyanti; Muhammad Wajdi; Nurul Magfirah; Nurul Fadhilah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Every day, the number of patients suffering from covid-19 continues to increase in the world. Learning at home is a decisive step in breaking the chain of Coronavirus spread, and changing traditional learning to entirely online can affect the quality of learning and students' achievement. It requires great effort in designing learning by lecturers. Therefore, a study is needed to investigate the students' perception of online learning to find out how the learning process went through by students during the covid-19 pandemic. This research uses a mixed-method approach. The first phase collects quantitative data using questioner with four dimensions: 1) the ability to learn independently through online learning, 2) student interaction with teaching materials, 3) interaction between students, and 4) interaction with lecturers. Based on data analyzed, students perceive that learning independently through online learning is not high, and scores obtained about 3.3 (average). The other three dimensions get a score that is in the low category. The second phase is collecting qualitative data using open-ended questions. Based on the analysis, the majority problem online learning is bad networking, and the positive impact students got in online learning is flexibility and time management in learning.